2020
DOI: 10.6065/apem.2040060.030
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density in children and adolescents with cancer

Abstract: Maximizing accumulation of bone mass during childhood and adolescence is essential to attaining optimal peak bone mass. Childhood cancer survivors (CCS) have lower bone mineral density (BMD) than the general population. Chemotherapeutic agents including steroids and radiotherapy can affect BMD. Cancer itself, hormonal insufficiency, a poor nutritional state, and a deficit of physical activities during or after treatment also influence BMD in CCS, resulting in failure to achieve appropriate peak bone mass. Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
(152 reference statements)
0
13
0
Order By: Relevance
“…Some studies reported that at 6 months after HSCT, nearly 50% of patients showed osteopenia at the femoral neck or lumbar spine. Almost one-third of allogeneic HSCT patients in childhood had reduced bone mineral density (BMD) before reaching adulthood, with a high prevalence of asymptomatic vertebral compression fractures [ 7 ]. Other long-term sequelae of cancer treatment, such as gonadal dysfunction, growth hormone deficiency, and altered body composition, have been shown to influence bone remodeling [ 5 ].…”
Section: Bone Metabolism and Physiopathology Of Osteoporosismentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies reported that at 6 months after HSCT, nearly 50% of patients showed osteopenia at the femoral neck or lumbar spine. Almost one-third of allogeneic HSCT patients in childhood had reduced bone mineral density (BMD) before reaching adulthood, with a high prevalence of asymptomatic vertebral compression fractures [ 7 ]. Other long-term sequelae of cancer treatment, such as gonadal dysfunction, growth hormone deficiency, and altered body composition, have been shown to influence bone remodeling [ 5 ].…”
Section: Bone Metabolism and Physiopathology Of Osteoporosismentioning
confidence: 99%
“…Estrogen has a role in attaining peak bone mass (PBM) in both sexes. Androgens enlarge the cross-sectional area of long bones and increase mechanical strength [ 7 ]. GH and insulin-like growth factor I are important for maintaining bone mass because both independently contribute to bone remodeling and apposition [ 1 ].…”
Section: Bone Metabolism and Physiopathology Of Osteoporosismentioning
confidence: 99%
See 2 more Smart Citations
“…ALL in childhood or adolescence is related to various endocrinopathies after the cessation of therapy, which may persist for several years (2). Most importantly, skeletal morbidities due to osteoporosis and vertebral fractures (VFs) caused by impaired mineralization are common endocrinologic complications that occur during and after ALL treatment (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%